(Un)making the upland: resettlement, rubber and land use planning in Namai village, Laos - Kramp, J.; Suhardiman, Diana; Keovilignavong, Oulavanh (Informa UK Limited, 2022)
This paper highlights how farmers in a northern Lao village transformed their customary land rights – in the face of incoherent overlapping state territorialization attempts – into a territorial strategy to secure their land tenure. By planting rubber, some villagers have engaged in a crop boom to lay claim to land which has recently been zoned for upland rice cultivation (and conservation) as part of a state-led land use planning initiative. We show how internal resettlement, ethnic division and the influx of commercial agriculture in the Lao uplands intersect in a novel land use planning process and predetermine the plan’s actual significance.